Biexponential R2* relaxometry for estimation of liver iron concentration in children: A better fit for high liver iron states. Issue 4 (5th April 2019) - Barrera, Christian A.; Khrichenko, Dmitry; Serai, Suraj D.; Hartung, Helge D.; Biko, David M.; Otero, Hansel J.
Abstract : Background: R2* relaxometry's capacity to calculate liver iron concentration (LIC) is limited in patients with severe overload. Hemosiderin increases in these patients, which exhibits a non‐monoexponential decay that renders a failed R2* analysis. Purpose/Hypothesis: To evaluate a biexponential R2* relaxometry model in children with different ranges of iron overload. Study Type: Retrospective. Population: In all, 181 children with different conditions associated with iron overload. Field Strength/Sequence: 1.5T, T2 *‐weighted gradient echo sequence. Assessment: Bi‐ and monoexponential R2* relaxometry were measured in the liver using two regions of interest (ROIs) using a nonproprietary software: one encompassing the whole liver parenchyma (ROI‐1) and the other only the periphery (ROI‐2). These were drawn by a single trained observer. The residuals for each fitting model were estimated. A ratio between the residuals of the mono‐ and biexponential models was calculated to identify the best fitting model. Patients with 1) residual ratio ≥1.5 and 2) R2*fast ≥R2*slow were considered as having a predominant biexponential behavior. Statistical Tests: Nonparametric tests, Bland–Altman plots, linear correlation, intraclass correlation coefficient. Patients were divided according to their LIC into stable ( n = 23), mild ( n = 58), moderate ( n = 61), and severe ( n = 39). Results: The biexponential model was more suitable for patients with severe iron overload when compared with the other three LIC categories ( P < 0.001) for both ROIs. For ROI‐1, 37 subjects met criteria for a predominant biexponential behavior. The slow component (5.7%) had a lower fraction than the fast component (94.2%). For ROI‐2, 22 subjects met criteria for a predominant biexponential behavior. The slow component (4.7%) had a lower fraction than the fast component (95.2%). The intraobserver variability between both ROIs was excellent. Data Conclusion: The biexponential R2* relaxometry model is more suitable in children with severe iron overload. Level of Evidence: 3 Technical Efficacy: Stage 1 J. Magn. Reson. Imaging 2019;50:1191–1198.